2022
DOI: 10.1002/ange.202116632
|View full text |Cite
|
Sign up to set email alerts
|

Thermal‐Triggered Dynamic Disulfide Bond Self‐Heals Inorganic Perovskite Solar Cells

Abstract: One great challenge for perovskite solar cells (PSCs) lies in their poor operational stability under harsh stimuli by humidity, heat, light, etc. Herein, a thermaltriggered self-healing polyurethane (PU) is tailored to simultaneously improve the efficiency and stability of inorganic CsPbIBr 2 PSCs. The dynamic covalent disulfide bonds between adjacent molecule chains in PU at high temperatures self-heal the in-service formed defects within the CsPbIBr 2 perovskite film. Finally, the best device free of encapsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 43 publications
(38 reference statements)
0
30
0
Order By: Relevance
“…[32,34] This property leads to the reconstruction of hydrogen bonds and the dynamic rearrangement of SS bonds happens, which involves the rupture of SS bonds in initial polymer chain and then cross-linkage with adjacent chain. [29,49] In this process, the material as a whole to maintain the original form, and no obvious phase transition or depolymerization effect (Figure S18, Supporting Information). Consequently, based on these dynamic chemical bonds, the crack could be repaired by a simple mild 65 °C treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[32,34] This property leads to the reconstruction of hydrogen bonds and the dynamic rearrangement of SS bonds happens, which involves the rupture of SS bonds in initial polymer chain and then cross-linkage with adjacent chain. [29,49] In this process, the material as a whole to maintain the original form, and no obvious phase transition or depolymerization effect (Figure S18, Supporting Information). Consequently, based on these dynamic chemical bonds, the crack could be repaired by a simple mild 65 °C treatment.…”
Section: Resultsmentioning
confidence: 99%
“…[28] On this basis, Zhang et al have designed a high temperature self-healing PU with dynamic covalent disulfide bonds (SS) between adjacent molecular chains to repair the in-service formed crystallographic defects at rigid all-inorganic devices. [29] However, self-healing under high-temperature or other extreme conditions will doubtless accelerate the ion diffusion to decompose perovskite and metal electrode, even damage the flexible substrate. Meanwhile, the self-healing capability of perovskite/ charge transport layer interface occupies the same important position as the bulk perovskite film, which is often overlooked in current studies.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] In the last few years, the power conversion efficiency (PCE) of perovskite solar cells (PSCs) has increased to 25.7% from 3.8% by adjusting the composition of perovskite materials and optimizing the interface and structure of PSC devices. [6][7][8][9][10][11] Currently, the shortcircuit current density (J SC ) is getting closer to the theoretical limit. 12 However, there is still a large gap between the opencircuit voltage (V OC ) and the theoretical value, which limits the PCE of PSCs.…”
Section: Introductionmentioning
confidence: 93%
“…Recently, the introduction of self‐healing polymers to improve the long‐term stability and durability of the PSCs has attracted wide attention 23–26 . Aiming at the perovskite film prone to cracks under the external force, Chen et al introduced self‐repairing polyurethane with a dynamic covalent oximecarbamate bond, which can achieve mechanical self‐healing under 100°C 23 .…”
Section: Introductionmentioning
confidence: 99%
“…17,22 Recently, the introduction of self-healing polymers to improve the long-term stability and durability of the PSCs has attracted wide attention. [23][24][25][26] Aiming at the perovskite film prone to cracks under the external force, Chen et al introduced self-repairing polyurethane with a dynamic covalent oxime carbamate bond, which can achieve mechanical self-healing under 100 C. 23 Zhao et al used self-healing polyethylene glycol to exhibit moisture resistance and self-repairing properties, which recovered rapidly after removal of water vapor. 25 Li et al reported a poly(vinyl alcohol) scaffold not only stabilized the FAPbI 3 films, but also self-healed in the wet environment.…”
Section: Introductionmentioning
confidence: 99%